Evolution of shocks and turbulence in major cluster mergers - Paul, Surajit; Iapichino, Luigi; Miniati, Francesco; Bagchi, J.; Mannheim, K. (The astrophysical journal, 2011)
We performed a set of cosmological simulations of major mergers in galaxy clusters, in order to study the evolution of merger shocks and the subsequent injection of turbulence in the post-shock region and in the intra-cluster medium (ICM). The computations have been performed with the grid-based, adaptive mesh refinement hydrodynamical code Enzo, using a refinement criterion especially designed for refining turbulent flows in the vicinity of shocks. When a major merger event occurs, a substantial amount of turbulence energy is injected in the ICM of the newly formed cluster. Our simulations show that the shock launched after a major merger develops an ellipsoidal shape and gets broken by the interaction with the filamentary cosmic web around the merging cluster. The size of the post-shock region along the direction of shock propagation is of the order of 300 kpc h−1, and the turbulent velocity dispersion in this region is larger than 100 km s-1. We performed a scaling analysis of the turbulence energy within our cluster sample. The best fit for the scaling of the turbulence energy with the cluster mass is consistent with M5/3, which is also the scaling law for the thermal energy in the self-similar cluster model. This clearly indicates the close relation between virialization and injection of turbulence in the cluster evolution. As for the turbulence in the cluster core, we found that within 2 Gyr after the major merger (the timescale for the shock propagation in the ICM), the ratio of the turbulent to total pressure is larger than 10%, and after about 4 Gyr it is still larger than 5%, a typical value for nearly relaxed clusters. Turbulence at the cluster center is thus sustained for several gigayears, which is substantially longer than typically assumed in the turbulent re-acceleration models, invoked to explain the statistics of observed radio halos. Striking similarities in the morphology and other physical parameters between our simulations and the “symmetrical radio relics” found at the periphery of the merging cluster A3376 are finally discussed. In particular, the interaction between the merger shock and the filaments surrounding the cluster could explain the presence of “notch-like” features at the edges of the double relics.